A U-shaped association between dietary inflammatory index and oral pain: a cross-sectional study from NHANES 2003–2018 - Sun, Honglan; Yang, Chao; Chen, Shizhao; Yin, Xiaoyunqing; Huang, Yuqi; Kuang, Huifang; Luo, Wen (Frontiers in Nutrition, 2025)
ObjectivesOral pain (OP) is a prevalent condition affecting one in four US adults, potentially influenced by diet through inflammation-related pathways. This study aimed to investigate the association between the Dietary Inflammatory Index (DII) and the prevalence of OP in a nationally representative sample.MethodsThis cross-sectional study included 23,869 participants from the 2003–2018 National Health and Nutrition Examination Survey (NHANES). OP was assessed via a self-reported question regarding the experience of OP in the past year. DII scores were calculated using data from two 24-h dietary recall interviews. Weighted multivariable logistic regression models and subgroup analyses were performed to evaluate the relationship between DII and OP. Restricted cubic spline analysis was used to examine the shape of the association.ResultsDII was positively associated with OP in the fully adjusted regression model (OR: 1.026, 95% CI: 1.001, 1.051). The association between DII and OP presented a U-shape, with a turning point of 0.95, indicating that both low and high levels of dietary inflammation were associated with an increased risk of OP. Subgroup analyses revealed no significant differences across different stratifications (p > 0.05 for all).ConclusionA U-shaped association between dietary inflammatory potential and oral pain was identified in this nationally representative sample. Encouraging a balanced diet that avoids both pro-inflammatory and excessively anti-inflammatory extremes may serve as a preventive or therapeutic strategy to alleviate oral pain and improve overall oral health outcomes.